Bcl‐2 protects TK6 cells against hydroquinone‐induced apoptosis through PARP‐1 cytoplasm translocation and stabilizing mitochondrial membrane potential. (26th August 2017) - Chen, Yuting; Chen, Shaoyun; Liang, Hairong; Yang, Hui; Liu, Linhua; Zhou, Kairu; Xu, Longmei; Liu, Jiaxian; Yun, Lin; Lai, Bei; Song, Li; Luo, Hao; et al.
Abstract : B cell leukemia/lymphoma‐2 (Bcl‐2) suppresses apoptosis by binding the BH3 domain of proapoptotic factors and thereby regulating mitochondrial membrane potential (MMP). This study aimed to investigate the role of Bcl‐2 in controlling the mitochondrial pathway of apoptosis during hydroquinone (HQ)‐induced TK6 cytotoxicity. In this study, HQ, one metabolite of benzene, decreased the MMP in a concentration‐dependent manner and induced the generation of reactive oxygen species (ROS), the activation of the DNA damage marker γ‐H2AX, and production of the DNA damage‐responsive enzyme poly(ADP‐ribose)polymerase‐1 (PARP‐1). Exposure of TK6 cells to HQ leads to an increase in Bcl‐2 and co‐localization with PARP‐1 in the cytoplasm. Inhibition of Bcl‐2 using the BH3 mimetic, ABT‐737, suppressed the PARP‐1 nuclear to cytoplasm translocation and sensitized TK6 cells to HQ‐induced apoptosis through depolarization of the MMP. Western blot analysis indicated that ABT‐737 combined with HQ increased the levels of cleaved PARP and γ‐H2AX, but significantly decreased the level of P53. Thus, ABT‐737 can influence PARP‐1 translocation and induce apoptosis via mitochondria‐mediated apoptotic pathway, independently of P53. In addition, we found that knockdown of PARP‐1 attenuated the HQ‐induced production of cleaved PARP and P53. These results identify Bcl‐2 as a protective mediator of HQ‐induced apoptosis and show that upregulation of Bcl‐2 helps to localize PARP‐1 to the cytoplasm and stabilize MMP. Environ. Mol. Mutagen. 59:49–59, 2018. © 2017 Wiley Periodicals, Inc.